The United States of America Foreign Policy in the Middle East through Bill Clinton presidential period between 1993 and 2000 - Weysi, Karwan S. (Humanities Journal of University of Zakho, 2018)
This article depicts the United States of America Foreign Policy in the Middle East through Bill Clinton presidential period between 1993 and 2000. This article has used some documents, reports, articles and secondary sources that are used for the first time for such a study. The Clinton administration foreign policy towards the Middle East is elaborated the United States of America’s position as a sole superpower of the world. The Clinton administration determined by democratizing, equality and peace attempted to open the Middle East. The unipolar world allowed the United States to visibly change its foreign policy with the aim of managing with the Middle East political state of affairs. The lack of having power against the shadow of superpower foreign policy in the region to corporate actions with the only capable power gave the United States of America to have abilities to open its armed forces centers in the Persian Gulf to shore up and contribute democratization, practice Dual Containment policy on Iraq and Iran, and develop the peace process of Arabs and Israelis. The United States increased its involvement in the Middle East to protect the region, generate stability, so acquired its position power in the unipolar world by distributing democratization, opening free markets and advocating peace process. The unipolar world has given increasing changes to the United States of America foreign policy strategy and allowed increasing its armed forces involvement to obtain its foreign policy initiatives.